A COMPARATIVE STUDY OF ORGANIC AND PHOSPHATE FERTILIZERS WITH IRRIGATION WATER QUALITY ON SOME SOIL PROPERTIES AND BEAN YIELD. - Shahad R. H. Muhammad,; Samira N. H. Al-Hassoon,; Sadeq J. H. Dwenee, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A factorial experiment was carried out in the Jisr Diyala region, east of Baghdad, to study a comparison of the types of organic fertilizers in interaction with the levels of phosphate fertilizer and the quality of irrigation water on some soil properties and yield of broad bean(Vicia faba L), using a randomized complete block design (RCBD) according to the split- split plot arrangement, and with three replications. Three factors were used, the first factor is water quality (well water and Diyala River water, I1 and I2) and the second is two types of organic fertilizers (control, sludge and sheep waste by 5 Mg ha-1, M0, M1 and M2) and the third is the addition of three levels of phosphorus (0, 80 and 160 kg ha-1, P0, P1, and P2) respectively. Seeds of faba bean (Vicia faba L.), cultivar Luz-de-otoho, were sown in winter season 2022, and analyzes were made for some physical and chemical properties of the soil after harvest. The results showed that the type of organic fertilizers had an effect on some chemical properties of the soil after harvest, as the electrical conductivity (EC) of the soil after harvest decreased significantly. The highest decrease was in the treatment I2M2P2, which amounted to 2.74 dS m–1, with a decrease of 52.10% compared to treatment (I1M0P0). The degree of soil reaction (pH) also decreased significantly, and the highest decrease was for treatment I1M2P2 at 7.41, with a decrease 3.89% compared to treatment (I2M0P0) . While the organic carbon increased significantly, and the highest significant increase was for the treatment I2M2P2 at 17.10 g Kgt-1, with an increase rate of 179.87% compared to treatment (I1M0P0). It was found that there was a significant effect on the dry pods weight, as the highest significant increase occurred when for the treatment I2M2P2 at 33.95 g plant-1, with an increase of 141.12% compared to treatment (I1M0P0) .